ANALISIS SISTEM PENGENDALIAN INTERN UNTUK PERSEDIAAN BARANG DAGANG PADA CV. PANCARAN JAYA ABADI BORONG - Sabu, Katarina S; Thalib, Sabra B W; Londa, Yulita (Program Studi Akuntansi Universitas Flores, 2021)
Effective and efficient control is needed by an organization or company because with the existence of an internal control system, it is hoped that everything that has been set can be implemented properly in order to avoid errors or fraud. Inventories are very important for trading companies because they are goods that are held for sale or used in the normal activities of the company. This study aims to determine how the implementation of an internal control system for inventory of merchandise at CV. Pancaran Jaya Abadi Borong, thus, getting a clear picture of the internal control for an inventory of merchandise that has been implemented. This research is a type of qualitative research. The data used are primary data and secondary data. Data collection techniques were carried out through interviews and documentation. The results showed that the internal control system for merchandise inventory at CV. Pancaran Jaya Abadi Borong is not in accordance with a good inventory accounting system so in carrying out activities there are double duty functions and errors in recording inventory. It is recommended that there should be a separation of task functions and special supervision of employees so that they can carry out their duties in accordance with the responsibilities of each function.